Mobile E-Based Search Engine by Image Mapping Using Binary Histogram Classification - Alkhatib, Deaa Eddin A. (2010)
Among the most popular in the World Wide Web are the sites that offer text-based search engines. Compared to text-based search engine, there are not many search engines that do image searching, face detection or image index searching. In this study, mobile-based search engine application by image mapping using binary histogram classification is proposed. This study will begin with the introduction section which will include a detailed explanation, definition on the history of text-based search engines. Next, the literature review and the methodology will be done. The final output of this project is a mobile-based image search engine prototype.